Exploring the Nexus between Regional Fiscal Capacity and the Convergence of Inclusive Economic Development - Rachmad Kresna Sakti; Nugroho Suryo Bintoro; Axellina Muara Setyanti; Rahayu Anzelina Agustin (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2024)
In the fiscal decentralisation system, the establishment of fiscal capacity is of paramount importance as local governments must be capable of effectively managing their own financial resources to meet the needs of the local population and advance regional development. Possessing a robust fiscal capacity enables local governments to be more effective in enhancing regional economic growth. This study analyses the influence of regional fiscal capacity on the convergence of inclusive economic development across 34 provinces in Indonesia. Conditional beta convergence analysis is employed on the Inclusive Economic Development Index, which is influenced by the degree of fiscal decentralisation, local financial autonomy, effectiveness of local own-source revenue, indirect expenditure ratio and direct expenditure ratio. This study provides valuable insights revealing visible convergence trends among Indonesia’s 34 provinces indicating crucial progress in achieving inclusive economic development and eliminating inequality. Furthermore, the observed progress underlines the vital role of fiscal capacity, particularly the levels of fiscal decentralisation and direct spending, as a significant driver encouraging a positive trajectory of economic convergence between provinces.